2005
DOI: 10.1037/0033-2909.131.6.856
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Major Assumptions About Behavior Change: A Comprehensive Look at the Effects of Passive and Active HIV-Prevention Interventions Since the Beginning of the Epidemic.

Abstract: This meta-analysis tested the major theoretical assumptions about behavior change by examining the outcomes and mediating mechanisms of different preventive strategies in a sample of 354 HIVprevention interventions and 99 control groups, spanning the past 17 years. There were 2 main conclusions from this extensive review. First, the most effective interventions were those that contained attitudinal arguments, educational information, behavioral skills arguments, and behavioral skills training, whereas the leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
644
3
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 678 publications
(713 citation statements)
references
References 263 publications
32
644
3
8
Order By: Relevance
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
See 3 more Smart Citations
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
“…For example, behavioral medicine researchers and practitioners have been found to report low confidence in their ability to replicate highly effective behavioral interventions for diabetes prevention [6]. The absence of standardized definitions and labels for intervention components means that systematic reviewers develop their own systems for classifying behavioral interventions and synthesizing study findings [7,8,9,10]. This proliferation of systems is likely to lead to duplication of effort and undermines the potential to accumulate evidence across reviews.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analyses of condom behavior studies revealed a central determining role for attitudes; if people hold a negative attitude about condoms they are unlikely to use them (Albaracín et al, 2005;Albaracín, Johnson, Fishbein, & Muellerleile, 2001;Sheeran, Abraham, & Orbell, 1999). A major limitation of the literature on condom-related attitudes, however, is its disregard of relational processes that influence condom use (Ciesla, Roberts, & Hewitt, 2004;Feeney & Raphael, 1992;WHO, 2012).…”
Section: Introductionmentioning
confidence: 99%